KONSTRUKSI MAHASISWA BROKEN HOME DI SURABAYA DALAM MEWUJUDKAN MASA DEPAN BERKELUARGA - Reino Aryo D, Muhammad Pahlevy (Paradigma, 2022)
Abstract The construction of individual thought becomes one of the basis for the individual to choose and determine a thing to be lived. The construction is formed based on time and the environment in which the individual adapts. Including each individual has his own thought construction on a marriage in each individual and also on the formation of a family. Marriage and family formation are things that are considered obligatory in the social environment so there is an assumption that every individual will experience it and each individual must carry out a marriage or family formation. Regarding this matter, it is a special concern for children who are large in coming from broken home families in terms of their construction of marriage as well as family formation. children from broken homes have fears and worries about marriage and family formation. such as preliminary research that has been done that the average broken home child has a fear of going into a marriage and forming a family in the future, they have a sense of trauma and fear of how to run a good family. The researcher uses a qualitative research method that uses a phenomenological approach and also uses a purposive technique approach. Based on the research that has been done, it is found that children living in broken home families have a fear of going to the marriage process and family formation, they think that they do not have the courage to go to marriage level. Although there are some of these children who already have a partner, they are still unsure and not sure about going to the level of marriage. And according to the results of the study it was found that children who live in broken homes think marriage or family formation is a complicated journey that requires a lot of preparation and consideration. Keywords: construction, child Broken Home, Family formation